一种变桨电机转矩输出能力评估方法及测试系统 (2023)
一种变桨电机转矩输出能力评估方法，包括以下过程：变桨电机在低频低转速下进行空载试验，根据所述的信息处理器采集到的电机端电压和定子电流，绘制变桨电机空载试验的端电压曲线，根据变桨驱动电机的等效电路及方程和变桨电机的等效参数绘制变桨电机空载试验的电动势曲线；根据电动势曲线和端电压曲线的趋近程度评估电机的转矩输出能力，即电动势曲线和端电压曲线之间的压差作为趋近程度的指标，指标越小表明转矩输出能力越好。以及一种实现变桨电机转矩输出能力评估方法的测试系统。本发明能有效评估变桨电机转矩输出能力。 A variable-pitch motor torque output capability assessment method includes that a variable-pitch motor is subject to a no-load test at low frequency and low rotating speed, an end voltage curve of the variable-pitch motor in the no-load test is drawn according to end voltage of the motor and stator current collected by an information collector, and an electromotive force curve of the variable-pitch motor in the no-load test is drawn according to equivalent circuit and equation of a variable-pitch driving motor and equivalent parameters of the variable-pitch motor; torque output capability of the motor is assessed according to approaching degree of the electromotive force curve and the end voltage curve, in other words, a pressure difference between the electromotive fo